COMPARISON OF SARS-CoV ANTIBODY TITER LEVELS AGAINST ABO BLOOD TYPE, AGE, AND GENDER IN CONVALESCENT PLASMA DONATIONS - Ariani, Resti; Puspita, Rina; Astuti, Anna Kartika Yuli; Lestari, Aulia Dewi; Dewi, Andriani Setiawan; Open, Maria Kurniati Manggina (MSJ : Majority Science Journal, 2024)
An important requirement to become a convalescent plasma donor is a standardized SARS-CoV antibody titer. However, not all Covid-19 survivors pass the plasma donor selection due to low antibody titer. This research aims to determine the comparison of SARS-CoV antibody titer levels with blood type, age and gender of Covid-19 convalescent plasma donors at blood donation unit PMI Semarang City. This study is an analytical observational study with a cross sectional design, using 300 data on convalescent plasma donors. The sampling technique used was purposive sampling. Differences in SARS-CoV antibody titer levels based on blood type, age, and gender were tested using SPSS 25. Donors involved in this study were divided based on the conversion of convalescent plasma titer levels, namely 1:80 (37%), 1:160 (4%), 1:250 (10.3%) and 1:640 (48.7%). Based on blood type data, most convalescent plasma donors have blood type O (42%) with the highest titer levels in the 1:640 category (48.7%). The highest mean titer level was found in blood group B which was 382.09. The results of the Kruskal-Wallis test showed no significant difference in titer levels by blood group, p=0.622 (>0.05). In the parameter of donor age, SARS-CoV antibody titer levels also showed no significant difference in donor age, both adolescent, adult and elderly donors with a value of p=0.598 (p>0.05). In line with these results, the chi square test of differences in antibody titres based on gender also showed no significant difference, p value=0.127 (p>0.05). High and low antibody titres of convalescent plasma donors are not determined by blood type, age and gender of the donor.